Day 1 Mon, May 02, 2016 2016
DOI: 10.4043/27255-ms
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating Wax Deposition From Crude Oils: Correlations Between Physical-Chemical Properties of Crude Oils and the Performance of Wax Inhibitors

Abstract: In this paper, we explore the correlations between the effectiveness of several wax inhibitors and physico-chemical properties of crude oils. First, the effects of the type of fluid was studied by dissolving refined paraffin waxes in non-waxy crude oils-here termed ЉdoctoredЉ crude oils-of different properties and comparing the wax appearance temperature and pour point of the doctored crude oils to those determined for a model waxy fluid used in previous studies [1]. After treating the doctored crude oils with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…The DSC results show that this wax consists of alkanes in the region around n -C40. This is consistent with other’s work that showed that wax inhibitors are less effective for waxes that have a carbon number greater than about C25. ,,,,, This suggests that WIA may not contain long enough aliphatic chains to adequately interact with the larger n -paraffins to cocrystallize with them. , …”
Section: Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…The DSC results show that this wax consists of alkanes in the region around n -C40. This is consistent with other’s work that showed that wax inhibitors are less effective for waxes that have a carbon number greater than about C25. ,,,,, This suggests that WIA may not contain long enough aliphatic chains to adequately interact with the larger n -paraffins to cocrystallize with them. , …”
Section: Resultssupporting
confidence: 87%
“…Since the HTGC work shows that the centrifuged waxes are enriched in >C28 n -paraffins, and considering that the WD Waxy B material is also enriched in the centrifuged waxes, then the WD Waxy B must also be likewise enriched in larger n -paraffinsor associated n -paraffin structuresof about C28 or larger. These results show that the WD is a convenient way to differentiate between crude oils that have more >C25 n -paraffins which are known to be difficult to treat with wax inhibitors . The data also show that the asphaltenes from the Minnelusa crude oil do not precipitate with, or are concentrated in, the centrifuged waxes.…”
Section: Resultsmentioning
confidence: 74%
See 3 more Smart Citations